Utilizing Amazon Web Services Tools for Efficient Multilingual Omnichannel Contact Centres - Mughele, Ese Sophia; Ogala, Justin Onyarin; Okpako, Ejaita Abugor (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2024)
A contact centre may face difficulties when there are language barriers between a customer and an agent. To improve customer experience, this study demonstrates how to instantly translate chat conversations between users in real-time, in their preferred language, across multiple channels. The paper used some essential Amazon Web Services (AWS) to implement this solution. At the core of the demo is our machine learning models, which help to auto-connect, evaluate and translate the customer experience. Researchers used Amazon Connect to modernize the information technology (IT) service desk with omnichannel contact centre capabilities. Customers could utilize Amazon Connect's flexible chat APIs to enable multilingual conversations. Developers can use Amazon serverless and API-based artificial intelligence/machine learning (AI/ML) services to incorporate machine learning capabilities into their apps.